Model Development Integrated Thematic Learning Based On Creative Thinking Stages On Elementary School Education - Faqih Hakim Hasibuan; Sri Minda Murni; Abdurrahman Adisaputera (International Journal of Educational Research & Social Sciences, 2021)
This research aims to describe the level of student activity in the learning process an integrated thematic learning model based on the stages of creative thinking in elementary school education. Learning carried out with separate subjects will cause less development of children to think holistically and make it difficult for students to relate concepts to their real life everyday. This research was carried out in Elementary School Patumbak sub-district, Deli Serdang Regency, North Sumatra Province. Implementation of this research conducted in even semester academic year 2020/2021. As for the location this research is focused at public elementary school 101788 Marindal I and public elementary school 101789 Marindal I. Besides students who are research subjects, then teacher too involved as research subjects subjek especially to see the implementation learning model in the implementation of learning and ability to manage learning. This type of research is development research. The resulting product is validated by design experts, linguist, and model expert, Then proceed with individual test, small group and field group test. Model implementation test carried out and then continued with the effectiveness test. This research findings: (1) thematic learning model products integrated based on the stages of creative thinking the result is valid based on expert validation, have a level of practicality and effectiveness on students' creative thinking stage, (2) creative thinking stage students increase with the N-Gain score is 0.50, (3) teacher's ability to manage learning very good with an average score of 3.62, (4) student learning activities during the learning process has increased, (5) student response to the learning process is good.